2021
DOI: 10.2174/1386207323666200526134512
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antidiabetic Potential of Armoracia Rusticana: Pharmacological and Computational Approach

Abstract: Aims & Objective: Armoracia Rusticana has high medicinal values and is an excellent source of phytochemicals. This study was aimed to evaluate the antidiabetic potential of bioactive compounds from Armoracia Rusticana. Methods: The antidiabetic analysis revealed Armoracia Rusticana was highly active against α-glucosidase with IC50 values of 5.6 µg/ml. Furthermore, molecular docking was used to identify the active constituents against α-glucosidase, while using acarbose as a controlled drug. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Isothiocyanates formed from the breakdown of GLS are responsible for most of the properties of Armoracia rusticana , including its taste and smell. Allyl isothiocyanate is the main compound causing the pungent taste and lacrimation [ 71 ]. These are volatile substances; therefore, the storage of horseradish, even in a cool room (5 °C), causes a reduction in their levels, even up to 50% [ 71 , 72 ].…”
Section: Composition and Antioxidant Potential Of Root Vegetablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Isothiocyanates formed from the breakdown of GLS are responsible for most of the properties of Armoracia rusticana , including its taste and smell. Allyl isothiocyanate is the main compound causing the pungent taste and lacrimation [ 71 ]. These are volatile substances; therefore, the storage of horseradish, even in a cool room (5 °C), causes a reduction in their levels, even up to 50% [ 71 , 72 ].…”
Section: Composition and Antioxidant Potential Of Root Vegetablesmentioning
confidence: 99%
“…Allyl isothiocyanate is the main compound causing the pungent taste and lacrimation [ 71 ]. These are volatile substances; therefore, the storage of horseradish, even in a cool room (5 °C), causes a reduction in their levels, even up to 50% [ 71 , 72 ].…”
Section: Composition and Antioxidant Potential Of Root Vegetablesmentioning
confidence: 99%
“…Similarly, various 1,2-benzothiazine 1,1-dioxides have been reported as antileukemic [25][26][27], 11β-HSD1 inhibitors [28], endotheline receptor antagonists [29], antimalarial agents [30], MAO inhibitors [31], antiallergic agents [32], antithrombotics [33], antiparasitic [34], antimicrobials [35,36], antioxidants [37], inhibitors of calpain I [38], and aldose reductase enzymes [39,40]. Our research group is involved in the search for novel and more effective antidiabetic agents [41][42][43][44][45], and in this context we have synthesized novel 1,2-benzothiazine-N-arylacetamides and screened them for their in silico and in vitro α-glucosidase inhibitory potential.…”
Section: Introductionmentioning
confidence: 93%
“…Our research group is involved in the search for novel and more effective antidiabetic agents [41][42][43][44][45], and in this context we have synthesized novel 1,2-benzothiazine-Narylacetamides and screened them for their in silico and in vitro α-glucosidase inhibitory potential.…”
Section: Synthetic Chemistrymentioning
confidence: 99%
“…Deoxy-nojirimycin (DNJ) is also a plant derived anti-diabetic compound isolated from Morus alba L. extract [ 26 ]. Recent studies have identified many phytochemicals from S.cumini with potential inhibitory activity against α-glucosidases and amylases [ 27 ].…”
Section: Introductionmentioning
confidence: 99%